Diabetic Ketoacidosis With Acute Pancreatitis in Patients With Type 2 Diabetes in the Emergency Department: A Retrospective Study - Ma, Li Ping; Liu, Xue; Cui, Bei Chen; Liu, Yan; Wang, Cong; Zhao, Bin (Frontiers in Medicine, 2022)
Objective: This study aims to explore the incidence and clinical features of acute pancreatitis (AP) in patients with type 2 diabetes diabetic ketoacidosis (DKA) in the emergency department, and discuss the predictive value of some pathological indicators for AP in DKA. Methods: Inpatient medical data of DKA patients hospitalized to our hospital's emergency department between January 2017 and January 2021 were evaluated retrospectively. These DKA patients were split into two groups based on whether they had AP or not. We examined the two groups' epidemiologic features, baseline laboratory results, and clinical outcomes. The Bedside Index for Sequential Organ Failure Assessment (SOFA), Acute Physiology and Chronic Health Evaluation II (APACHE II), and Logistic Organ Failure System (LODS) scores were computed and compared across groups. Results: The prevalence of AP in DKA patients was 15.53%. The difference in Abdominal pain between the two groups of patients was statistically significant (p<0.001), and there was no statistical difference in age, gender, and BMI. The DKA and AP group LOS (P<0.001), ICU admission rate (P=0.046), anion gap (P<0.001), red blood cell (P=0.002), hemoglobin (P<0.001), hematocrit(P =0.002), Serum triglyceride(P<0.001), Serum cholesterol(P<0.001), Serum amylase(P=0.004), Random glucose(P=0.028), Plasma fibrinogen(P<0.001), HbA1c(%)(P =0.008) higher than the DKA group, PH(P<0.001), CO2CP(P<0.001), Ca2+(P=0.022), Na+(P=0.001), Correction Na(P=0.034) lower than the DKA group. Multivariate analysis showed that low PH (P<0.05), hypertriglyceridemia (P=0.001), and hypercholesterolemia (P=0.010) were risk factors for DKA combined with AP. ROC curve analysis showed that the three Cut-off value: serum triglycerides of 10.52mmol/L, serum cholesterol of 9.03mmol/L, and PH of 7.214. Serum triglyceride has the largest area under the curve (0.930). Under this cut-off value, the sensitivity (80%) and specificity of Serum triglyceride The degree (93.7%) is the highest, and the positive predictive value (62.0%) and negative predictive value (94.7%) of Serum cholesterol are the highest. Conclusions: A severe episode of DKA with significant acidosis and hyperlipidemia is more likely to be linked with AP. The frequently used critical illness score is ineffective in determining the severity of the condition. When the serum triglyceride cut-off value is 10.52mmol/L, it has a higher predicted value for AP in DKA.